Alzheimers Disease - An Update - Rahman, Aminur; Salam, Farhana; Islam, Md Aminul; Anwarullah, AKM; Islam, Md Rafiqul; Miah, Md Nurul Amin; Saha, Uttam Kumar; Ali, Zahed (Bangladesh Journal of Neuroscience, 2013)
Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 52-58